The intersection of race and femininity in the classroom - Faber, Naomi S.; Williams, Monnica T. (Frontiers in Psychology, 2023)
• Race as a discussion topic is actively avoided or derailed by White students; women strategically use their gender to this end • There is societal deference towards the visible distress made by a White woman in public that is not afforded other racial groups • This knowledge is used strategically by White women with and without their conscious intent to decenter people of color and center themselves Authorship: Both authors contributed equally to the writing and editing of the manuscript and the first author (NF) created the graphics which are original artwork.Contribution to the Field: Race as a classroom discussion topic is often avoided or derailed by students and faculty alike. Many White women have strategically used their gender to this end, aided by societal deference towards displays of visible distress (e.g., crying). This mechanism for enlisting support is not as easily afforded other racial groups. White femininity can be weaponized with or without conscious intent to decenter others and center themselves. Because some White students may come from areas demographically devoid of people of color, they may for the first time be involved in discussions about race in the college setting. If White students are allowed to derail such discussions and if faculty are not competent to intervene, this does a disservice to the people of color and impedes learning. This piece will raise awareness of these issues to help prevent their occurrence.